Rectification - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Masum, Ahmad; Arowosaiye, Yusuf Ibrahim (CLJ Malaysia Sdn Bhd, 2024)
T his chapter generally discusses an equitable remedy, i.e., rectification of instruments, available under the Specific Relief Act 1950. As it is an equitable remedy, wherein, in a proper case, the court may exercise its discretion to amend the language of a contract or instrument to make it in accordance with the true intention of the parties.1 In other words, rectification is a discretionary equitable remedy whereby an instrument that fails to accurately express the intention of the parties may be corrected.2 Thus, the court must first ascertain what that intention was and secondly, be satisfied that the words of the contract or instrument fail to express that intention. The court may either treat the contract retrospectively as if drawn in its rectified form or rectify an agreement and order specific performance.3 What is corrected is not mistake in the contract entered by the parties, but the instrument recording it.